A COMPARATIVE RESEARCH ON META-DISCOURSE MARKERS USED IN INTRODUCTION SECTION ON LOCAL, NATIONAL AND INTERNATIONAL JOURNAL ARTICLES OF ENGLISH EDUCATION - Hairiyanto M.Pd; Alamsyah Harahap; Dedi Sofyan (English Education Study Program Faculty of Teacher Training and Education, 2020)
This research aims to identify the meta-discourse feature mostly used and the difference between interactive and interactional categorize among Local, National and International Journals. This research was a corpora analysis employed journal articles as the object of the research. Data were collected purposive random sampling with a total of sampling were 30 articles taken three journals. The data is a cropped introduction section to be made a Microsoft file and processed by using the AntConce Application. Data were analyzed using a qualitative method by focusing on the use of the meta-discourse feature and different interactive and interactional categorized by Hyland’s (2005). The results show that: 1) The meta-discourse feature that is mostly used in each journal is interactive. The interactive has the same tendency used among Local, National and International journals. 2) The transition categorizes the most frequent in the Local, National and International Journal. 3) The meta-discourse feature that is least used was found in the Asian EFL Journal, the frame markers that are least used were found in Joall journals, and the endophoric that is the least used was found in Joall journals. 4) There are significant differences in the use of interactive and interactional in each journal. So it can be concluded that each writer has known and used meta-discourse in writing articles, the use of meta-discourse is not influenced by the level of journals, both Local, National and International Journal, but is influenced by the writer competence in expressing his thoughts, and the culture of the author's environment. Besides, the articles published in each journal are influenced by the editor of the journal itself.